Bricks and blueprints: methods and standards for DNA assembly - Casini,A; Storch,M; Baldwin,GS; Ellis,T (Nature Reviews Molecular Cell Biology, 2015)
DNA assembly is a key part of constructing gene expression systems and even whole chromosomes. In the past decade, a plethora of powerful new DNA assembly methods — including Gibson Assembly, Golden Gate and ligase cycling reaction (LCR) — have been developed. In this Innovation article, we discuss these methods as well as standards such as the modular cloning (MoClo) system, GoldenBraid, modular overlap-directed assembly with linkers (MODAL) and PaperClip, which have been developed to facilitate a streamlined assembly workflow, to aid the exchange of material between research groups and to create modular reusable DNA parts.